Play! A Special Issue - Bem Caroline; Paasonen Susanna (SAGE Publications Ltd, 2025)
Sexuality, as it relates to video games in particular, has received increasing attention over the past decade in studies of games and play, even as the notion of play remains relatively underexplored within sexuality studies. This special issue asks what shift is effected when sexual representation, networked forms of connecting and relating, and the experimentation with sexual likes are approached though the notion of play. Bringing together the notions of sex and play, it both foregrounds the role of experimentation and improvisation in sexual pleasure practices and inquires after the rules and norms that these are embedded in.
Contributors to this special issue combine the study of sexuality with diverse theoretical conceptions of play in order to explore the entanglements of affect, cognition, and the somatic in sexual lives, broadening current understandings of how these are lived through repetitive routines and improvisational sprees alike. In so doing, they focus on the specific sites and scenes where sexual play unfolds (from constantly morphing online pornographic archives to on- and offline party spaces, dungeons, and saunas), while also attending to the props and objects of play (from sex toys and orgasmic vocalizations to sensation-enhancing chemicals and pornographic imageries), as well as the social and technological settings where these activities occur. This introduction offers a brief overview of the rationale of thinking sex in and as play, before presenting the articles that make up this special issue.